Sublethal Effect of Pyriproxyfen Released From a Fumigant Formulation on Fecundity, Fertility, and Ovicidal Action in Aedes aegypti (Diptera: Culicidae) - Harburguer, Laura Vanesa (2014)
Dengue and dengue hemorrhagic fever are mosquito-borne viral diseases that coincide with the distribution of Aedes aegypti (L.), the primary vector in the tropical and semitropical world. With no available vaccine, controlling the dengue vector is essential to prevent epidemics. The effects of the insect growth regulator pyriproxyfen on Ae. aegypti adults that survived a treatment with a sublethal dose were investigated in the laboratory, including effects on their reproductive potential. Pyriproxyfen was released from a fumigant formulation at a dose causing 20 or 40% emergence inhibition (%EI). Females were dissected before and after blood feeding and the basal follicle number was counted. There were no differences between the control and treated group on the basal follicle number for both doses used. Fertility and fecundity were reduced at a concentration of EI40 but no at EI20. There was no ovicidal effect of pyriproxyfen by immersion of eggs in treated water neither when the females laid their eggs on a pyriproxyfen-treated surface. This work shows that sublethal doses of pyriproxyfen can have effects on fertility and fecundity ofAe. aegypti females, which together with its larvicidal activity could contribute to an overall decrease in a given population.